Wellness monitoring for professional ballet dancers: a pilot study - Harrison, C.; Ruddock, S.; O'Halloran, P.; Mayes, S.; Cook, J.; Ruddock-Hudson, M. (Journal of Dance Medicine & Science, 2021)
Self-report wellness measures are used extensively in elite sport as valid indicators of the adaptive responses to training and performance of an athlete. Wellness parameters such as quality and quantity of sleep, muscle soreness, fatigue, and stress are monitored in professional sport via Athlete Management Systems (AMS) and self-report monitoring applications (App). However, the use of a monitoring App specifically for professional classical ballet dancers has not been tested. This study piloted a self-report App to measure wellness constructs in a professional ballet company. Three male and two female dancers volunteered to take part in the mixed-method study, entering daily wellness data, frequency of work-related activities, and injury status into an App on their smart phones. Via a focus group interview session, perceptions of wellness and experiences using the App were found to be favorable, with dancers reporting that the App enhanced awareness of their well-being. To further develop monitoring tools in professional ballet companies, it is recommended that the App be made specific to the wellness needs of dancers.